Below the Surface: Comparing Legislative History Usage by the House of Lords and the Supreme Court - James J. Brudney (Washington University Law Review, 2007)
This Article offers the first empirical examination of how often, and in what ways, Britain’s highest court has used previously excluded legislative history materials in its judicial decisions. It also represents the first effort to compare legislative history treatment between the Law Lords and the Supreme Court. The Article’s comparative inquiry identifies differences in the frequency with which legislative history is invoked in each Court’s decisions and offers explanations for the distinct patterns of usage that have emerged. Part I of the Article presents recent developments in Britain, including the basic rule of Pepper v. Hart and some key modifications or refinements of the rule announced in subsequent decisions. Part II begins with a quantitative comparison between the Law Lords’ invocation of Hansard since 1996 and the Supreme Court’s use of legislative history during the same time period. Part II then considers whether there are sound reasons for British courts to rely less on legislative history than do American courts. The comparison focuses on the nature of the legislative process in the two countries and on separation of powers issues, including the risks of opportunistic behavior by creators of legislative history. Part III examines certain elements of the current debate among British judges, using these elements to anticipate future uses of Hansard by the Law Lords. Part III also identifies differences between the British and American approaches that may be instructive for the Supreme Court in one respect and for the Law Lords in another.
Keywords: Legislative histories; Legislative histories – Great Britain; United States. Supreme Court; Great Britain. Parliament. House of Lords